Macroeconomic Behaviour and Economic Growth in Ghana - Daniel Agyapong; Anokye Mohammed Adam; Michael Asiamah (SPOUDAI - Journal of Economics and Business, 2016)
This study tries to ascertain the behaviour of some major macroeconomic factors that would drive Ghana's economic growth using Johansen approach to cointegration. The study uses quarterly data from 1980:Q1 to 2013:Q4. The data were first analyzed using the Augmented Dickey Fuller (ADF and Philips-Perron (PP) tests which indicate that all the variables of interest were stationary after theifirst differencing. The study found cointegration relationship between real GDP (economic growth and its macroeconomic factors. The study found that in the long run physical capital, labour force, real effective exchange rate, stock market prices have positive effects on real GDP growth while consumer price index, interest rate, money supply, and government expenditure have negative effects on real GDP growth .In the same way, in the short run, physical capital, labour force, real effective exchange rate, stock market prices have positive effects on real GDP growth while consumer price index interest rate, money supply, and government expenditure still had negative effects on real GDP growth. Based on the study findings, it recommended that the Government together with the Bank of Ghana should develop and pursue prudent both fiscal and monetary policies that would aim at stabilising the macroeconomic indicators.
Keywords: E1; E13; E6; 330; Macroeconomic; Cointegration; Unit Root Tests; Economic Growth; Time Series